Implementasi E-Government Berbasis Android Untuk Meningkatkan Pelayanan Publik - Susianto, Didi; Ridhawati, Eka; Sucipto, Sucipto (Universitas Al Azhar Indonesia, 2022)
Technology in government is a breakthrough in managing and disseminating information about government to the public. The existence of technology that is applied in a government hope can provide flexibility and transparency for the community and complete complex tasks. The purpose of this study is to build an Android-based e-government information system in Tanjung Rejo Village that can provide services and information to the people of Tanjung Rejo Village and the general public. Data collection methods used in this study were observation, documentation, interviews, and literature study. While the method used in designing e-government by following the information system development life cycle (System Development Life Cycle), generally consists of the stages of analysis, design, implementation, and use. The case study of this research is e-government in Tanjung Rejo village. This research can produce an e-government planning document in Tanjung Rejo village. From the results of the e-government design in Tanjung Rejo village, it is hoped that it will make it easier for village officials or residents to convey and obtain information related to Tanjung Rejo village quickly and accurately. An Android-based e-government information system can be used and applied in the process of submitting village activity and potential data. Further research can be developed by adding several more varied features and can add mobile GIS and GPS systems.Keywords - E-government, Public service, Information system, Utilization of information technology